Genetic risk factors for chronic obstructive pulmonary disease (Faculty of Medicine Universitas Indonesia, 2001)
Chronic obstructive pulmonary disease (COPD) is a complex condition, influenced by environmental and/or genetic risk factors. It is important to identify these factors, and develop new therapies for the management of COPD. This review identifies these factors and highlights the role they will play in future treatment options of COPD. (Med J Indones 2001; 10: 178-81)